Perancangan Desain Proposal Pelatihan UMKM 2023 Kota Surabaya - Naila Safira (Institut Nalanda, 2023)
The presence of Micro, Small and Medium Enterprises (MSMEs) has a central role in a sustainable economic structure. At the local level, they also contribute to community vitality, create social bonds, and promote economic independence. Therefore, planning the training proposal design has an important role in the implementation of training activities. Design planning including layout, typography, illustrations, color selection plays a big role in the implementation of these training activities. This is because the design of the proposal is able to invite MSMEs to take part in training activities. If the design is not good then the target (SMEs) will have difficulty reading and understanding the purpose of making the proposal and the target will not even be interested in reading it. Therefore, this design has an important role in the sustainability of an activity.